Multi-color flow cytometry for evaluating age-related changes in memory lymphocyte subsets in dogs. (October 2018) - Withers, Sita S.; Moore, Peter F.; Chang, Hong; Choi, Jin W.; McSorley, Stephen J.; Kent, Michael S.; Monjazeb, Arta M.; Canter, Robert J.; Murphy, William J.; Sparger, Ellen E.; Rebhun, Robert B.
Abstract: While dogs are increasingly being utilized as large-animal models of disease, important features of age-related immunosenescence in the dog have yet to be evaluated due to the lack of defined naïve vs. memory T lymphocyte phenotypes. We therefore performed multi-color flow cytometry on peripheral blood mononuclear cells from young and aged beagles, and determined the differential cytokine production by proposed memory subsets. CD4+ and CD8+ T lymphocytes in aged dogs displayed increased cytokine production, and decreased proliferative capacity. Antibodies targeting CD45RA and CD62L, but less so CD28 or CD44, defined canine cells that consistently exhibited properties of naïve-, central memory-, effector memory-, and terminal effector-like CD4+ and CD8+ T lymphocyte subsets. Older dogs demonstrated decreased frequencies of naïve-like CD4+ and CD8+ T lymphocytes, and an increased frequency of terminal effector-like CD8+ T lymphocytes. Overall findings revealed that aged dogs displayed features of immunosenescence similar to those reported in other species. Highlights: Phenotypic markers defining memory T lymphocyte subsets were evaluated in dog PBMCs. CD45RA and CD62L expression delineated canine T cells with distinct functions. CD4+ and CD8+ naïve T cells decreased, and CD8+ TEMRA T cells increased in old dogs. Canine lymphocytes display features of immunosenescence that mirror those in humans.